Introduction Of Shrink Uncertainty For Downsizing The Order Of Large Scale Interval Systems (Journal of Namibian Studies : History Politics Culture, 2023)
In this paper, a new approach for downsizing the order of large-scale interval systems has been proposed by introducing the shrink uncertainty for the formulation of Routh-table. The proposed method utilizes two conditions for limiting the range of interval coefficients. The existing Routh approximation and modified Routh approximation methods used for the order reduction of interval systems were insufficient to hold the stability of system. This new approach holds the interval limit as we move down in Routh-table and guarantees stable downsized model for stable large-scale system. A numerical example is considered to show the supremacy of the proposed method over existing methods by comparing the time response specifications and error indices.